2017
DOI: 10.1016/j.lwt.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Use of a lytic bacteriophage to control Salmonella Enteritidis in retail food

Abstract: A Salmonella Enteritidis lytic bacteriophage designated as SE07 was isolated from retail meat samples. Electron micrograph revealed that phage SE07 belonged to family Podoviridae. Phage SE07 was relatively stable at the temperature ranging from 28 to 65 °C. Furthermore, it exhibited remarkable pH stability (between pH 4.0-11.0). The effectiveness of phage SE07 was determined in different food matrices (fruit juice, fresh eggs, beef and chicken meat) experimentally contaminated with S. Enteritidis. A significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 12 publications
2
46
0
2
Order By: Relevance
“…In addition, their ability to withstand acid is also an important quality for therapeutic purposes. Almost similar results were reported for other Salmonella phages . S. Enteritidis phages PA13076 and PC2184 were stable between pH 6–9 and 5–11, respectively .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, their ability to withstand acid is also an important quality for therapeutic purposes. Almost similar results were reported for other Salmonella phages . S. Enteritidis phages PA13076 and PC2184 were stable between pH 6–9 and 5–11, respectively .…”
Section: Discussionsupporting
confidence: 85%
“…The head diameter and tail lengths of SE‐P3, P16, P37, and P47 varied between 65 ± 2.06–83 ± 3.09 and 43 ± 2.41–109 ± 3.09 nm, respectively. Most of the identified Salmonella phages are tailed viruses of various lengths with double‐stranded DNA genomes and belong to three families of the Caudovirales order, including Myoviridae (long hard‐contractile tailed), Siphoviridae (long non‐flexible contractile), and Podoviridae (short nontapered tailed) . It was reported that 91% of 177 Salmonella phages belonged to the Caudovirales order and 24% of them were in Myoviridae , 31% were in Siphoviridae and 33% were in Podoviridae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was reduced by 1.14 and 4.52 log CFU/cm 2 by a phage at MOIs of 10 4 and 10 5 , respectively. Thung et al (2017) also reported that S. Enteritidis in chicken meat was reduced by 2.0 log CFU/g by a phage at an MOI of 10 7 . Based on our results, high titers of phages (MOIs of 10 5 and 10 6 ) were found to be effective in this regard.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the types of phages and bacteria present in a community determine the antibacterial spectrum of the treatment. Previous studies have shown that bacteriophages can be effective against some bacterial species on meat samples (Liu et al., ; Thung et al., ; Yeh et al., ). However, in most of these studies only 1 strain of bacteria was tested, and when the effectiveness of a dual bacteriophage cocktail was tested against 4 different Salmonella serovars, exposure only reduced bacterial numbers by 1 log cycle (Yeh et al., ).…”
Section: Antibacterial Biomoleculesmentioning
confidence: 99%